2019
DOI: 10.1158/1541-7786.mcr-19-0493
|View full text |Cite
|
Sign up to set email alerts
|

The Notch Pathway Promotes Osteosarcoma Progression through Activation of Ephrin Reverse Signaling

Abstract: Despite significant advancements in the diagnosis and treatment of osteosarcoma, the molecular mechanisms underpinning disease progression remain unclear. This work presents strong clinical and experimental evidence demonstrating that Notch signaling contributes to osteosarcoma progression. First, using a cohort of 12 patients, Notch genes were upregulated in tumors compared with adjacent normal tissue, and high tumor expression of Notch1 intercellular domain (NICD1) and the Notch target gene Hes1 correlated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…As a result, we highlighted JMJD2C and HIF1α as downstream signaling molecules of miR-216b, wherein miR-216b reduced JMJD2C expression, likely interfering with mRNA stability and JMJD2C action in the demethylation of HES1 gene at the promoter region. More importantly, high expression levels of HES1 have been previously correlated with enhanced OS cell proliferation, migration and invasion as well as boosted chemoresistance [44]. What's more, our findings revealed that miR-216b diminished the expression of HES1 via the removal of H3K9 methylation at the gene promoter site of HES1 in OS cells, which has been previously emphasized as a critical factor for HES1 activation [27].…”
Section: Discussionsupporting
confidence: 67%
“…As a result, we highlighted JMJD2C and HIF1α as downstream signaling molecules of miR-216b, wherein miR-216b reduced JMJD2C expression, likely interfering with mRNA stability and JMJD2C action in the demethylation of HES1 gene at the promoter region. More importantly, high expression levels of HES1 have been previously correlated with enhanced OS cell proliferation, migration and invasion as well as boosted chemoresistance [44]. What's more, our findings revealed that miR-216b diminished the expression of HES1 via the removal of H3K9 methylation at the gene promoter site of HES1 in OS cells, which has been previously emphasized as a critical factor for HES1 activation [27].…”
Section: Discussionsupporting
confidence: 67%
“…Through the synergistic effect among different drugs, the multi-drug treatment can improve the therapeutic effect, reduce adverse reactions, and inhibits the occurrence of drug resistance, which may be an effective strategy to overcome the insufficient treatment of cisplatin [48,49]. Recent studies showed that Notch may be involved in the mechanism of cisplatin resistance [50,51], and γ-secretase is a key enzyme in the activation of the Notch pathway, and its specific inhibitor DAPT can block the activation of Notch signaling [52]. However, the role of Notch signaling pathway in the mechanism of cisplatin resistance remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling is important in the maintenance of stem cells in intestinal crypts, by regulating the expression of EphrinB1, where the reciprocal gradients of EphB2 and EphrinB1 define the balance of intestinal stem cell self-renewal and differentiation ( 90 ). In cancer context also Notch1 is reported to regulate EphrinB1 signaling, as shown in osteosarcoma ( 91 ). Notably, another tubulin isotype, βIVb is shown to directly regulate EphrinB1 surface localization in oral cancer stem cells and their niche ( 5 ).…”
Section: Tubulins Implicated In the Regulation Of Cscs And Their Nichementioning
confidence: 98%